ANALISIS HUBUNGAN KUALITAS PRODUK, PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA KONSUMEN ALFABIAH COOKIEES) - Arnida Arnida; Tamrin Meda; Sabridah (AkMen JURNAL ILMIAH, 2023)
The Cookies or pastries business is a trending business which lately has had quite a lot of interest among the public. It is clear that there are many offers for the public to consume cookies, not only during holidays or during certain events. However, over time, cookies became a daily snack. This makes the demand for cookies in the community to be high. The research aims to determine the variables that influence customer satisfaction. This research was conducted to determine whether product quality, service quality, price and promotion affect customer satisfaction at Alfabiah Cookees Store. This research uses multiple linear regression analysis to measure the influence of these elements. so based on the analysis, it can be concluded that simultaneously there is an influence of product quality variables (X1), service quality (X2), price (X3), and promotion (X4). Affect customer satisfaction (Y), where the results show the most significant impact on customer satisfaction of alphabiah cookies shop cake products.